2012
DOI: 10.1002/ange.201205317
|View full text |Cite
|
Sign up to set email alerts
|

[(NHC)Yb{N(SiMe3)2}2]‐Catalyzed Cross‐Dehydrogenative Coupling of Silanes with Amines

Abstract: Selten aktiv: [(NHC)Yb{N(SiMe3)2}2]‐Addukte (NHC=N‐heterocyclisches Carben) sind effiziente Katalysatoren für die katalytische dehydrierende Kreuzkupplung von Silanen mit primären und sekundären Aminen. Die Reaktion gelingt unter milden Bedingungen und liefert die Silylamine in hohen Ausbeuten (82–100 %). Die katalytische Aktivität und Selektivität der Seltenerdmetallsilylamide kann über die Sterik des NHC‐Liganden moduliert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…As a contrast, tribenzylyttrium complex without an auxiliary ligand was also investigated, which failed to achieve the catalytic dehydrogenative coupling reaction even at elevated temperature (Table , entries 5–6). Similar ligand accelerating effect was also reported by Crimmin and Cui using a phosphorus based ligand and a NHC ligand . Using the yttrium complex ( 2 d ) as catalyst, we further carried out the silylamination reaction of methylphenylsilane ( 3 b ) and tert ‐butylamine.…”
Section: Figuresupporting
confidence: 67%
“…As a contrast, tribenzylyttrium complex without an auxiliary ligand was also investigated, which failed to achieve the catalytic dehydrogenative coupling reaction even at elevated temperature (Table , entries 5–6). Similar ligand accelerating effect was also reported by Crimmin and Cui using a phosphorus based ligand and a NHC ligand . Using the yttrium complex ( 2 d ) as catalyst, we further carried out the silylamination reaction of methylphenylsilane ( 3 b ) and tert ‐butylamine.…”
Section: Figuresupporting
confidence: 67%
“…4,5 Aminosilane compounds have traditionally been synthesised via aminolysis, a process that generates HCl as a side product (eqn (2)). Efforts to provide an alternative route to Si-N bonds using N-H/Si-H dehydrocoupling reactions (eqn (3)) have largely involved catalysts such as (Ph 3 P)RhCl, 6 Cu(I)Cl, 7 (NHC)Yb[N(SiMe 3 ) 2 ] 2 8 (NHC = N-heterocyclic carbene) and [(Et 2 N)U][BPh 4 ]. 9 Apart from the applications of non-metal based Frustrated Lewis Pairs (FLPs), 10 main group catalysed Si-N coupling has so far focused on s-block metal reagents.…”
Section: E-mentioning
confidence: 99%
“…In this reaction, approximately 2% conversion to Ph{N(SiMe 3 ) 2 }SiH 2 was observed. 18 Neither MePh{N-(SiMe 3 ) 2 }SiH nor Ph 2 {N(SiMe 3 ) 2 }SiH were observed in the reaction between methylphenylsilane or diphenylsilane with diethylamine, respectively. 43 In addition, there are no cases in which bis(trimethylsilyl)amine was coupled with silamine products.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 In 2012, Cui and co-workers demonstrated that a different ytterbium catalyst, [IMesYb{N(SiMe 3 ) 2 } 2 ] (IMes = 1,3dimesitylimidazol-2-ylidene), could successfully heterodehydrocouple primary and secondary silanes with amines. 18 Sadow has expanded upon Si−N coupling with lanthanides, reporting that [Ln{C(SiHMe 2 ) 3 } 2 ImtBu] (Ln = Yb, Sm; ImtBu = 1,3-ditert-butylimidazol-2-ylidene) are also active catalysts for this transformation. 19 To date, however, there are no reports of more abundant lanthanides catalyzing the heterodehydrocoupling of silanes and amines.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation